“Fear” and “Angst” in the Martin Heidegger’s Thought: from the “Existential Analytic” to the “Turning-Point” Thinking - Imbriano, Gennaro (Governare la paura. Journal of interdisciplinary studies, 2010)
The essay explores the philosophical concepts of fear (Furcht) and Angst, so as they are elaborated in the thought of Martin Heidegger. In particular, the author first lingers over the use of these concepts that are to be found in the pages of Sein und Zeit; secondly, he analyses its further elaboration considering the following Heideggerian shift to a reading of history of metaphysics as a history of Being.